The Impact of Folklore-Based Storytelling on Empathy Behavior in Kindergarten Children - Putri, Sekaringsih Angrenggani Cahyanti; Ayriza, Yulia; Khumalo, Jan; Joitun, Feuna Anasius (Universitas Muhammadiyah Yogyakarta, 2024)
Empathy, a moral emotion that enables individuals to understand and respond to others' emotions, is essential for fostering positive behavior and preventing harm. Storytelling, particularly folklore, can effectively develop empathy in children by immersing them in relatable narratives that encourage empathetic responses and social-emotional skills. This research aims to assess the impact of folklore as a storytelling method on children's behavior in kindergarten. The research used a quantitative method. Accordingly, this experimental research employed a Non-Equivalent Control Group Design with six treatments, with each experimental group and control group consisting of 10 children. This study analyzed empathy behavior data collected through observations using Wilcoxon Mann-Whitney tests. The results showed that the pretest score for the experimental class was 15.50. After the treatment, the score increased to 28.70. In comparison, the control class had a pretest score of 16.10 and a posttest score of 16.90. The Wilcoxon test resulted in an Asymp.Sig (2-tailed) value = 0.005. The hypothesis test conducted resulted in a significant value of 0.005, which meant Ho was rejected (p 0.05). This study found that there was an increase in the use of storytelling because it can foster children's imagination and help children better understand the message in the story. This research is expected to assist other schools in addressing the problems experienced by students.